2010
DOI: 10.1007/s10875-010-9470-x
|View full text |Cite
|
Sign up to set email alerts
|

RANTES Deficiency Attenuates Autoantibody-Induced Glomerulonephritis

Abstract: Experimental autoimmune nephritis in mice and spontaneous lupus nephritis are both associated with elevated expression of several chemokines in the kidneys. Nevertheless, the role that different chemokines play in mediating renal inflammation is far from complete. This study focuses on elucidating the functional role of RANTES, a chemokine that has been noted to be hyper-expressed within the kidneys, both in experimental renal disease as well as in spontaneous lupus nephritis. To elucidate if RANTES was essent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 35 publications
1
14
0
Order By: Relevance
“…CCL5 expression in the glomerulus has also been documented previously (6, 10, 2224). Thus, we chose to investigate if a disruption in Fli-1 expression affects CCL5 production in vitro ; we performed transfection studies using Fli-1 specific siRNA and negative control siRNA in murine endothelial MS1 cells.…”
Section: Resultssupporting
confidence: 72%
See 2 more Smart Citations
“…CCL5 expression in the glomerulus has also been documented previously (6, 10, 2224). Thus, we chose to investigate if a disruption in Fli-1 expression affects CCL5 production in vitro ; we performed transfection studies using Fli-1 specific siRNA and negative control siRNA in murine endothelial MS1 cells.…”
Section: Resultssupporting
confidence: 72%
“…A variety of renal diseases have been linked to the CCL5 gene (21) and its’ expression has been documented in the kidney cortex, glomerulus, and renal tubular epithelial cells (5, 6, 10, 20, 2224). Analysis of microarray data from glomerular gene expression in MRL/ lpr mice, a murine model of lupus, with active lupus nephritis demonstrated a profound up-regulation of CCL5 mRNA (24).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anti-GBM-GN has been used as a model for the study of lupus nephritis because the two conditions share some common molecular pathways [11]. Our previous study showed that anti-GBM antibody challenge induced severe GN in some mouse strains such as 129/svj, DBA1, and NZW, whereas some other strains, such as B6 and BALB/c, were resistant to anti-GBM challenge, exhibiting no or very mild GN [12].…”
Section: Introductionmentioning
confidence: 99%
“…RANTES is an important chemotactic molecule for T cells and plays an active role in leukocyte recruitment and the development of LN, as demonstrated in a RANTES-defficient murine model, which developed milder renal disease upon induction of an immune complex-mediated nephritis [127]. Along those lines, urinary CD4 + T cells were recently described as an additional tool for the identification of LN in adult SLE patients [128].…”
Section: Promising Experimental Biomarkers For Lupus Nephritismentioning
confidence: 99%